Coadministration of Ketamine and Perampanel Improves Behavioral Function and Reduces Inflammation in Acute Traumatic Brain Injury Mouse Model. (12th December 2020) - Alqahtani, Faleh; Assiri, Mohammed A.; Mohany, Mohamed; Imran, Imran; Javaid, Sana; Rasool, Muhammad Fawad; Shakeel, Waleed; Sivandzade, Farzane; Alanazi, Ahmed Z.; Al-Rejaie, Salim S.; Alshammari, Musaad A.; Alasmari, Fawaz; et al.
Abstract : Traumatic brain injury (TBI) is among the most debilitating neurological disorders with inadequate therapeutic options. It affects all age groups globally leading to post-TBI behavioral challenges and life-long disabilities requiring interventions for these health issues. In the current study, C57BL/6J mice were induced with TBI through the weight-drop method, and outcomes of acutely administered ketamine alone and in combination with perampanel were observed. The impact of test drugs was evaluated for post-TBI behavioral changes by employing the open field test (OFT), Y-maze test, and novel object recognition test (NOR). After that, isolated plasma and brain homogenates were analyzed for inflammatory modulators, i.e., NF- κ B and iNOS, through ELISA. Moreover, metabolomic studies were carried out to further authenticate the TBI rescuing potential of drugs. The animals treated with ketamine-perampanel combination demonstrated improved exploratory behavior in OFT (P < 0.05 ), while ketamine alone as well as in combination yielded anxiolytic effect (P < 0.05 ‐ 0.001 ) in posttraumatic mice. Similarly, the % spontaneous alternation and % discrimination index were increased after the administration of ketamine alone (P < 0.05 ) and ketamine-perampanel combination (P < 0.01 ‐ 0.001 ) in the Y-maze test and NOR test, respectively. ELISA demonstrated the reduced central and peripheral expression of NF- κ B (P < 0.05 ) and iNOS (P < 0.01 ‐ 0.0001 ) after ketamine-perampanel polypharmacy. The TBI-imparted alteration in plasma metabolites was restored by drug combination as evidenced by metabolomic studies. The outcomes were fruitful with ketamine, but the combination therapy proved more significant in improving all studied parameters. The benefits of this new investigated polypharmacy might be due to their antiglutamatergic, antioxidant, and neuroprotective capacity.